Hambatan Mahasiswa Praktik Pengalaman Lapangan Bimbingan Konseling Sekolah (PPLBKS) dalam Pemberian Layanan Bimbingan Kelompok (Studi Terhadap Mahasiswa PPLBKS Semester Ganjil 2013/2014) - Diana, Diana; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
The problem in this research is the trouble that occur by the students (PPLBKS) when they do field training in giving group guidance and conseling. Significance of this research to describe 1) the trouble that face by the students of PPLBKS in conducting group guidance. 2) the trouble that face by the students of PPLBKS in appearing group dinamic when serve group guidance. The methodology of this research is descriptive that try to describe situation. The technique that apply in this researche is the simple random sampling. The population in this research are all of the students of PPLBKS 2013/2014, the number of the students are 197 students. Furthermore, the sample of this research are 66 students. The instruments of this research is questionaire. In addition, an analisys of this research is percent formula. The finding of this research are 1) the trouble that face by the students in understanding the implementation of group guidance and conseling have much trouble. 2) the trouble that face by the students of PPLBKS in appearing group dinamic when serving group guidance is more enough.